Characterization of Nandidurga and Bidri goat populations of Karnataka - TANTIA, M S; VIJ, P K; YATHISH, H M; KULKARNI, V S; SHETTAR, V B; GOPALA, G T; SHARMA, HIMANI; SHARMA, REKHA (The Indian Journal of Animal Sciences, 2018)
Nandidurga and Bidri goat populations are known to exist in Karnataka but were not studied earlier. Phenotypic as well as genetic characterization revealed these two goat populations to be uniform and distinct from other neighbouring goats. Bidri is a medium sized black goat with higher fecundity and are distributed in Bidar district of Karnataka and adjoining areas. Bidri is meat type goat with 50% dressing percentage. Nandidurga is white coloured and distributed in Chitradurga district of Karnataka. This is also meat type goat with similar dressing percentage. Both these populations have higher fecundity and twinning is very common. Reasonable polymorphism in Bidri goats was evident as mean number of observed alleles was 8.48±0.88 with ILSTS033 showing the highest (16) allele number per locus. Expected number of alleles varied from 1.043 (OarJMP29) to 8.804 (OMHC1) with mean of 3.58±0.44. Similarly, Nandidurga population had 8.22±0.66 mean observed number of alleles. Estimates of observed heterozygosity (0.58±0.06 and 0.60±0.05 for Bidri and Nandidurga respectively) confirmed the sufficient level of diversity in the two populations. Heterozygote deficit in these populations was also not significant being 2.5% in Nandidurga and 3.9% in Bidri goats. Distinctness of the two goat populations can be assumed on the basis of assignment tests and principal coordinate analyses. This information on the genetic analysis can be used in conjunction with the information on physical and phenotypic characteristics and management practices for registration of these populations as breeds.